Rotational dynamics between bureaucracy and electocracy - I. A. Lavrov (Цифровая социология)
It is generally believed that, based on the principle of separation of powers, the branches of government are endowed with independence from each other and equality among themselves, which means that they can control and balance each other’s activities. This principle can also be considered true for politicians, representatives of each of the branches of government. Bureaucrats holding positions in the executive branch are politically equal to electocrats in the legislative branch. At the same time, bureaucrats and electocrats are politicians of different kinds, they have a large number of differences in their powers, functions, rights, and competencies. But does this principle remain immutable for the Russian political system de facto? Are bureaucrats and electocrats so different from each other in Russia? The present study, analyses the biographies of 800 politicians of the Russian Federation who hold public positions in the executive and legislative authorities of all three levels: federal, regional, and municipal. The analysis allowed us to reveal the specifics of recruitment and circulation of personnel in the Russian political system, which makes it possible to speak with a high degree of probability about the trends in the development of the Russian establishment as a whole.